Risk factors for agitation in home-cared older adults with dementia: evidence from 640 elders in East China - Liu, Jiaxin; Lin, Taoyu; Liu, Guanjun; Dong, Xiaoxin; Min, Rui (Frontiers in Neuroscience, 2023)
Background: Agitation is common among older adults with dementia, negatively affecting their quality of life and their caregivers’. Since home care remains the dominant approach for older adults, this study investigates the risk factors for agitation in older adults with dementia in China. Methods: We perform a cross-sectional study of home-cared older adults with dementia in Ningbo, China, using 2020 data. We use a self-made questionnaire to investigate the risks of agitated behaviour and its related factors. We perform descriptive, univariate, and regression analyses. Findings: We address 876 older Chinese adults; 41.6% of the sample exhibits one or more agitated behaviors. We find that basic health issues, such as dementia type, activities of daily living (ADL), family support issues, such as Zarit Burden Interview (ZBI) scale and Family APGAR Questionnaire (APGAR), and behavioural awareness issues, such as fall and scald, significantly influence the occurrence of agitation behaviors (P<0.05). Older adults with mixed AD-VaD dementia (MD), poor ADL, heavy ZBI, severe APGAR and a history of fall or scald are more likely to exhibit agitated behaviors(P<0.05). Interpretation: Agitated behaviour in home-cared older adults with dementia are diverse and closely related to mental state, family support, and behavioural awareness issues. Caregivers, often family members, should be attentive to the needs of dementia patients and take active and effective measures to improve their quality of life. They should be aware of the causes and triggers of agitated behaviour and take steps to reduce its occurrence.